Genome and Comparative Transcriptome Dissection Provide Insights Into Molecular Mechanisms of Sclerotium Formation in Culinary-Medicinal Mushroom Pleurotus tuber-regium - Sun, Xueyan; Wu, Junyue; Zhang, Shuhui; Luo, Lu; Mo, Cuiyuan; Sheng, Li; Ma, Aimin (Frontiers in Microbiology, 2022)
Pleurotus tuber-regium is an edible and medicinal sclerotium-producing mushroom. The sclerotia of this mushroom can serve as food and folk medicine. Based on the description of monokaryon genome sequenced with Illumina and PacBio sequencing technologies, the comparative transcriptomic analysis using RNA sequencing (RNA-seq) was employed to study the mechanism of sclerotia formation. The de novo assembled genome is 35.82 Mb in size with a N50 scaffold size of 4.29 Mb, and encodes 12,173 putative proteins. Gene expression analysis demonstrated that 1,146 and 1,249 were up-regulated and down-regulated expression in newly formed sclerotia compared with mycelia, respectively. The differentially expressed genes (DEGs) are associated with the substrate decomposition, oxidation-reduction process, cell wall synthesis, and other biological process, suggesting that these genes and pathways may affect sclerotia formation in P. tuber-regium. These genomic and transcriptomic resources will provide useful information for the molecular biology study underlying the sclerotia formation in P. tuber-regium.